Principles and challenges of applying epigenetic epidemiology to psychology. - Jones, Meaghan J.
The interplay of genetically driven biological processes and environmental factors is a key driver of research questions spanning multiple areas of psychology. A nascent area of research focuses on the utility of epigenetic marks in capturing this intersection of genes and environment, as epigenetic mechanisms are both tightly linked to the genome and environmentally responsive. Advances over the past 10 years have allowed large-scale assessment of one epigenetic mark in particular, DNA methylation, in human populations, and the examination of DNA methylation is becoming increasingly common in psychological studies. In this review, we briefly outline some principles of epigenetics, focusing on highlighting important considerations unique to DNA methylation studies to guide psychologists in incorporating DNA methylation into a project. We discuss study design and biological and analytical considerations and conclude by discussing interpretability of epigenetic findings and how these important factors are currently being applied across areas of psychology. -- (from the author)